Clinical spectrum of cryoglobulinaemic neuropathy. Issue 10 (16th September 2005) - Gemignani, F; Brindani, F; Alfieri, S; Giuberti, T; Allegri, I; Ferrari, C; Marbini, A
Abstract : Background and objective: Cryoglobulinaemic neuropathy (CN) is probably common, as it is usually related to HCV infection. The aim of this study was to delineate the clinical spectrum of CN in a large series and to investigate the factors influencing its expression. Methods: Seventy one consecutive patients (12 men, 59 women), diagnosed as having CN on the basis of clinical features of neuropathy, clinical and serological findings of mixed cryoglobulinaemia, and exclusion criteria, were identified during a six year period. All patients underwent clinical examination, and electrophysiological and laboratory investigations. Results: Results of the patients with "pure" CN (n = 54) and those with comorbidities (n = 17) were evaluated separately. Of the former 76% had sensory neuropathy (including selective small fibre sensory neuropathy (SFSN) in 14 patients), 15% had sensorimotor polyneuropathy, and 9% had mononeuritis multiplex. The pattern of distribution was similar in the patients with comorbidities. In 30/54 patients, CN was the first manifestation of cryoglobulinaemia. Patients with mild cryoglobulinaemic syndrome had sensory neuropathy more frequently than patients with active syndrome (p<0.001), in particular SFSN (p<0.001). The latter group had more severe features, with significantly more cases of reduced or absent motor (p = 0.028) and sensory action potentials (p<0.001), and a tendency towards higher Rankin scores (p = 0.06). Conclusions: Sensory neuropathy, often in the form of SFSN, is by far the commonest form of CN. Cryoglobulinaemia should be vigorously investigated in the diagnosis of sensory neuropathy, especially in older women. Activity of the cryoglobulinaemic syndrome is a major factor influencing the clinical expression and severity of CN.